Pengaruh Media Video Animasi Terhadap Karakter Peduli Lingkungan Di Taman Kanak-Kanak Kartika 1-63 Kota Padang - Sari, Fadillah; Hartati, Sri (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
This research is motivated by the underdeveloped character of caring for the environment in children. This is caused by the low initial understanding of children towards environmental care behaviors that they usually do routinely. The main objective of the study was to determine the effect of the use of animated video media on environmental care characters in Kindergartens. The research method used was a quasi-experimental pretest-posttest nonequivalent control group design. The place of this research is Kartika 1-63 Kindergarten, Padang City. The sample consisted of 20 children consisting of the 5-6 year age group, namely the experimental class B1 and the control class B2. The data collection tool uses a rating scale. Then the data was analyzed using the T test (Independent Sample T-test) but beforehand it had gone through the normality prerequisite test, homogeneity to know how much influence the animated video media had on the character of caring for the environment in Kindergarten. The final results of this study showed a significance (2-tailed) of 0.016 <0.05 with an average N-Gain of 51.17% for the experimental class and 33.40% for the control class, so that the environmental care character of children treated with media animated videos are higher than the environmental care characters for children who use conventional media. As for the magnitude of the influence of animated video media based on the effect size test, it was obtained 1.4 (strong category). The conclusion obtained is that the animated video media has a very large and significant influence on the character of caring for the environment in kindergarten